2018
DOI: 10.1038/s41598-018-26740-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of genetics on third molar agenesis

Abstract: The purpose of this investigation was to determine the impact of heritability on third molar agenesis in twins. The study sample consisted of 284 same sex twins (172 monozygotic and 112 dizygotic), whose mean ages were 19.7 ± 4.3 and 18.9 ± 4.8 years, respectively. The monozygotic group consisted of 36.3% males and 63.7% females, while the dizygotic group consisted of 50.1% males and 49.9% females. The zygosity of the twins was established using 15 specific DNA markers. The prevalence of third molar agenesis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Indeed, this is also supported by the increased number of missing third molars in the agenesis sample compared to that expected by chance. A recent study analyzing data from 172 monozygotic and 112 dizygotic twins concluded that third molar formation is strongly controlled by additive genetic factors, providing further support to our statements (Trakinienė et al, 2018). This concept is in line with the evolutionary trend in humans towards less teeth, and more specifically, less molars (Kavanagh, Evans & Jernvall, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, this is also supported by the increased number of missing third molars in the agenesis sample compared to that expected by chance. A recent study analyzing data from 172 monozygotic and 112 dizygotic twins concluded that third molar formation is strongly controlled by additive genetic factors, providing further support to our statements (Trakinienė et al, 2018). This concept is in line with the evolutionary trend in humans towards less teeth, and more specifically, less molars (Kavanagh, Evans & Jernvall, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, this is also supported by the increased number of missing third molars in the agenesis sample compared to that expected by chance. A recent study analysing data from 172 monozygotic and 112 dizygotic twins concluded that third molar formation is strongly controlled by additive genetic factors, providing further support to our statements (Trakinienė et al 2018). This concept is in line with the evolutionary trend in humans towards less teeth, and more specifically, less molars (Kavanagh et al 2007).…”
Section: Discussionsupporting
confidence: 85%
“…Carabelli's trait, along with certain molar variants, received much attention (Alvesalo et al, ; Berry, ; Biggerstaff, , ; Kaul, Sharma, Sharma, & Corruccini, ; Laatikainen & Ranta, ; Mizoguchi, ; Scott & Potter, ; Sofaer, MacLean, & Bailit, ). More recently, sophisticated model‐fitting approaches have become the norm, such as path analysis and structural equation modeling (Hughes, Vo, Mihailidis, & Townsend, ; Townsend & Martin, ; Townsend et al, ; Trakinienė et al, ), as well as variance components analysis via maximum likelihood estimation (Paul, Stojanowski, Hughes, Brook, & Townsend, ; Stojanowski et al, ).…”
Section: Introductionmentioning
confidence: 99%